ANALISIS KELAYAKAN USAHA KECIL RFP WAROENG TANSU - Hafiza Aprilia; Fadil Abdullah; Siti Nurhamidah (Politeknik META Industri Cikarang, 2025)
that offers traditional ketan (sticky rice) dishes with modern toppings. The study explores whether the business can sustain profitability and growth in Bandung’s competitive culinary market local. The research problem focuses on determining whether Waroeng Tansu Om RFP is financially feasibility. The novelty in its focus integrates traditional culinary practices with modern digital strategies like food delivery platforms and proposes a dedicated business app. The research using method of market analysis (segmentation, targeting, and positioning) and financial feasibility assessment using. Data on costs, revenues, and customer demographics were analyzed. The findings reveal a positive NPV of Rp 1,131,557,216, an IRR of 79%, and a payback period within 3 years, with a BCR greater than 1, suggesting financial feasibility. The study concludes that Waroeng Tansu Om RFP is a viable business with potential for growth. The key takeaway is that combining traditional foods with modern innovations can lead to success in competitive markets